Determinants of Mothers' Motivation in Preventing Malnutrition In Toddlers: A Cross-Sectional Study - Istiana Kusumastuti; Sobar Sobar; Nurul Dwi Octaviani (Jurnal Kebidanan dan Kesehatan Tradisional, 2026)
Background: Malnutrition in children under five remains a persistent public health problem in Indonesia, influenced by various multidimensional factors. Maternal knowledge, perception, and both health worker and family support play critical roles in determining mothers’ motivation to prevent malnutrition. This study aimed to analyze the determinants influencing maternal motivation in preventing malnutrition among children under five. Methods: This quantitative cross-sectional study involved 98 mothers of children under five in the working area of Sukaresmi Health Center, Cianjur. Respondents were selected using a purposive sampling technique based on predefined inclusion criteria. Data were collected using a structured questionnaire and analyzed using multiple linear regression with SPSS software. Results: The findings revealed that maternal motivation was significantly influenced by knowledge (p = 0.007), perception (p = 0.016), health worker support (p = 0.048), and family support (p = 0.044). These four factors collectively explained 72.3% of the variance in maternal motivation to prevent malnutrition. Conclusion: Strengthening maternal capacity through health education, improving the quality of health services, and fostering supportive family environments are essential strategies to enhance maternal motivation and reduce malnutrition rates among children under five. The study underscores the need for comprehensive, family-centered, community-based interventions to address the multifactorial nature of child malnutrition.